Implementasi Program Pirus (Pipir Di Urus) Di Desa Ciwaru Kecamatan Ciemas Kabupaten Sukabumi - Nabhil Fadil Fauzan; Muhammad Syahidan F; Taufik Fajar Ramadhan (PT. Alahyan Publisher Sukabumi, 2023)
This service aims to increase food security at the family level in Ciwaru Village, Ciemas District, Sukabumi Regency so that household food needs can be met. Apart from that, through the PIRUS program, it is hoped that it will be able to add a source of side income for the residents of Ciwaru Village, Ciemas District, Sukabumi Regency. The service method used is the delivery of material through printed media in the form of brochures and focused discussions directly in the field with the community, before doing these two things, the facilitator, in this case, the student, has created a pilot garden in a place that is easily accessible to the community and approved by the relevant Village apparatus. The participants who took part in the PIRUS activity were residents of the Ciloa hamlet, Ciwaru Village, Ciemas District, Sukabumi Regency. The end result of this activity is that the community becomes more aware of the potential of the yard they have and understands more about food security within the family sphere. Apart from that, by utilizing this yard, it is hoped that they can meet the food needs of the family while reducing expenditure on food spending for daily consumption.